PENGARUH PEMBERIAN KOMPOS KULIT DURIAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BUNCIS RAMBAT ( PHASEOLUS VULGARIS L.) - IRAWATY ROSALYNE (JURNAL ILMIAH MAKSITEK, 2020)
This research was conducted in the district of Saribu Asih Hatonaman,, Simalungun regency with a height of 350 masl from January to April 2017. Using a random draft group (RAK) Non factorial with 5 treatment ie: K0: Without the introduction of compost, the skin of the durian, K1: compost the skin with a dose of 1.5 kg/plot, K2: Compost the skin with a dose of 2.25 kg/plot, K3: The compost of leather with the dose 3 kg/plot. 3.75. The parameters observed in this study were: height of the plant (cm), number of primary branches (fruit), weight of cropping pods samples (g), weight pods per plot (kg). The results of various analyses showed that durian compost is a real effect on all observation parameters. Test result of different average showed at the treatment of K4 (25 tons/ha of leather compost durian) obtained the highest crops on 2 and 4 MST (44.22 cm and 99, 93cm), Number of the most primary branches (6.69 rods), the weight of pods per crop of the highest sample (345 G or 2.45 ton/ha) and weight pods per plot highest (2.75 kg or 2.29 tons/ha).